2010
DOI: 10.1002/ab.20348
|View full text |Cite
|
Sign up to set email alerts
|

Support for religio‐political aggression among teenaged boys in Gaza: Part I: psychological findings

Abstract: Politically aggressive militant groups usually rely on support from a larger community, although evidence suggests that only some members of that larger community support that aggression. A major subtype of political aggression is that associated with religious differences--or Religio-Political Aggression (RPA). Little previous research has explored demographic or psychological factors that might distinguish supporters from non-supporters of RPA. In an exploratory study, we investigated whether factors previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 117 publications
4
33
1
2
Order By: Relevance
“…Although previous studies of terrorists have not shown significantly greater levels of severe mental illness (for example, psychoses with delusions and hallucinations), small studies of convicted terrorists and of teenagers in Palestine have suggested depressive and anxiety symptoms are important [23] [13]. One study seeking to define religious terrorism proposed the presence of ‘dogma induced psychotic depression’ but this investigation was not based on a structured diagnostic or screening instrument.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although previous studies of terrorists have not shown significantly greater levels of severe mental illness (for example, psychoses with delusions and hallucinations), small studies of convicted terrorists and of teenagers in Palestine have suggested depressive and anxiety symptoms are important [23] [13]. One study seeking to define religious terrorism proposed the presence of ‘dogma induced psychotic depression’ but this investigation was not based on a structured diagnostic or screening instrument.…”
Section: Discussionmentioning
confidence: 99%
“…Social explanations and psychiatric opinions abound when known terrorists face conviction [20], yet there are few empirical population studies that investigate these possible explanations for radicalisation and terrorism [21], [22]. One exception is an exploratory study of 52 teenage boys in Gaza that found depressive symptoms were common in supporters of ‘religio-political aggression’, whilst anxiety was heightened amongst Palestinian supporters of radical action [23]. Another interesting study used convergence of psychometric measures from 356 suicide-bombers, tapes of self-immolations of 15 terrorists, and 918 ‘zealots’ in order to isolate risk factors [24].…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to extreme ethnic-political violence seems to interfere with the child’s cognitive and emotional processing of those experiences and leads to the three hallmark criteria for post-traumatic stress disorder (Diagnostic and Statistical Manual of Mental Disorders; American Psychiatric Association, 2000): re-experiencing the event (e.g., intrusive memories, dreams); avoidance of stimuli associated with the events and emotional numbing; and symptoms of increased arousal (e.g., hypervigilance, irritability, sleep problems). Regarding youth in the Middle East, although a few studies have shown that the majority of youth exposed to extreme political violence in Gaza (e.g., bombardment of homes) exhibit PTSD (Qouta, Punamaki, & El Sarraj, 2003; Thabet, Tawahina, El Sarraj, & Vostanis, 2008), in general, the studies have shown only modest to moderate correlations between exposure and PTS symptoms (e.g., Abdeen, Qasrawi, Nabil, & Shaheen, 2008; Barber & Schluterman, 2009; Qouta, Punamaki, & El Sarraj, 2008; Slone, 2009; Thabet, Ibraheem, Shivram, Winter, & Vostanis, 2009; Victoroff et al, 2010), suggesting that there is remarkable resilience among youth. This has prompted researchers to stress the urgent need to identify factors that promote resiliency (Barber, 2009; Sagi-Schwartz, 2008; Seginer, 2008).…”
Section: Youths’ Exposure To Ethnic-political Conflict/violence and Pmentioning
confidence: 99%
“…Other emotional and/or experiential factors might also play a role. Victoroff et al. (2010), for example, recently found that, among 14‐year‐old boys in Gaza, anxiety and reported wounding or death of a family member by the Israeli Defense Forces were both associated with support for religio‐political aggression.…”
Section: Introductionmentioning
confidence: 99%